Gender differences and generation of ideas on civic crowdsourcing? - Bernardino, Susana (2019)
Crowdsourcing platforms are being used to increase citizens engagement with the development and implementation of new projects that are able to improve community’s wellbeing. The use of civic crowdsourcing has also been extended to the younger segments of the population, such as the Youth Participatory Budgeting in Portugal. This research aims to study the ideas developed by young citizens in order to understand whether gender is able or not to influence the ideas generated by the applicants. The study uses a quantitative approach to explore the database of proposals made to this crowdsourcing program. The results show that young men are more involved in the submission of new ideas than women. Also, some differences were found concerning the location and features of the territory where the opportunities are seized, in accordance with gender. No other significant differences were found in the ideas generated, such as number of proponents, geographical scope, theme or budget involved.